Recent Positive Selection in Genes of the Mammalian Epidermal Differentiation Complex Locus - Goodwin, Zane A.; de Guzman Strong, Cristina (Frontiers in Genetics, 2017)
The Epidermal Differentiation Complex (EDC) is the most rapidly evolving locus in the human genome compared to that of the chimpanzee. Yet the EDC genes that are undergoing positive selection across mammals and in humans are not known. We sought to identify the positively selected genetic variants and determine the evolutionary events of the EDC using mammalian-wide and clade-specific branch- and branch-site likelihood ratio tests and a genetic algorithm branch test. Significant non-synonymous substitutions were found in filaggrin, SPRR4, LELP1, and S100A2 genes across 14 mammals. By contrast, we identified recent positive selection in SPRR4 in primates. Additionally, the genetic algorithm branch test discovered lineage-specific evolution for distinct EDC genes occurring in each of the nodes in the 14-mammal phylogenetic tree. Multiple instances of positive selection for FLG, TCHHL1, SPRR4, LELP1, and S100A2 were noted among the primate branch nodes. Branch-site likelihood ratio tests further revealed positive selection in specific sites in SPRR4, LELP1, filaggrin, and repetin across 14 mammals. However, in addition to continuous evolution of SPRR4, site-specific positive selection was also found in S100A11, KPRP, SPRR1A, S100A7L2, and S100A3 in primates and filaggrin, filaggrin2, and S100A8 in great apes. Very recent human positive selection was identified in the filaggrin2 L41 site that was present in Neanderthal. Together, our results identifying recent positive selection in distinct EDC genes reveal an underappreciated evolution of epidermal skin barrier function in primates and humans.